1874-75 N.C. Sess. Laws 18 - (:unkn) unknown (My University, 1874)
Ch. 21, §§ 1-2: That the auditor of the State is hereby authorized and directed to issue his warrant upon the public treasurer for the payment of such sums as may be certified by the adjutant general and governor, and as may be actually necessary to pay the freight and drayage upon the public arms received as the quota of North Carolina, from the United States government, under the acts making provision for the arming of the militia of the several States and territories, or returned to the arsenals of the United States for exchange under the act of Congress of one thousand eight hundred and seventy-three.
Keywords: TRANSFER, MANUFACTURE & POSSESSION